ENGLISH OUTDOOR CLASS AT REMOTE AREA SCHOOL - Masruddin, Masruddin (Institut Agama Islam Negeri Palopo, 2016)
This research aimed at finding out whether the application of outdoor program is effective or not to build studentsâ vocabulary at the remote area school.Â In this research, the researcher applied a pre-experimental method. Pre-experimental design used pre-test and post-test where pre-test was held before treatment and post-test after treatment. This research was conducted in SMP Limbong especially in the outdoor of the first year students. The researcher chose SMP Limbong because the school was located in the remote area with many natural environments surrounding the school. The population of this research was the first year students of SMPN 2 Limbong. There is only one class. Thus, the total number of population of this research was 17 students. The researcher took all of the population as sample. So, the total number of sample was 17. The instrument that was used in collecting data in this research was vocabulary test. The result of the research shows that the application of environmental study outdoor is effective in building studentsâ vocabulary to the second year students of SMPN 2 Limbong. It was proven by the fact that there was a significant difference between the studentsâ mean score of the pretest and the posttest. In the pretest, the studentsâ mean score is 50.33 and the studentsâ score in posttest is 78.99. Moreover, it also could be seen by comparing the result of t-test and t-table where t-test is higher than t-table (9.672.093). It means that the hypothesis is received (tt Â > t0).This research aimed at finding out whether the application of outdoor program is effective or not to build studentsâ vocabulary at the remote area school.Â In this research, the researcher applied a pre-experimental method. Pre-experimental design used pre-test and post-test where pre-test was held before treatment and post-test after treatment. This research was conducted in SMP Limbong especially in the outdoor of the first year students. The researcher chose SMP Limbong because the school was located in the remote area with many natural environments surrounding the school. The population of this research was the first year students of SMPN 2 Limbong. There is only one class. Thus, the total number of population of this research was 17 students. The researcher took all of the population as sample. So, the total number of sample was 17. The instrument that was used in collecting data in this research was vocabulary test. The result of the research shows that the application of environmental study outdoor is effective in building studentsâ vocabulary to the second year students of SMPN 2 Limbong. It was proven by the fact that there was a significant difference between the studentsâ mean score of the pretest and the posttest. In the pretest, the studentsâ mean score is 50.33 and the studentsâ score in posttest is 78.99. Moreover, it also could be seen by comparing the result of t-test and t-table where t-test is higher than t-table (9.672.093). It means that the hypothesis is received (tt Â > t0).